Implementasi Pembelajaran Akhlak Tasawuf dalam Meningkatkan Karakter Demokratis Mahasiswa PAI FITK UNSIQ 2023 - Ahmad Aqif Syauqi; H. Abdul Majid; Chairani Astina (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research discusses the importance of the Akhlak and Tasawuf courses in Islamic Religious Education (PAI), aiming to teach moral values to students and enhance their character. Issues such as declining character, lack of participation, and poor relationships with lecturers remain concerns. Students need guidance to apply good morals according to the teachings of the Quran and Sunnah. Tasawuf emphasizes inner purity and closeness to Allah through praiseworthy traits like patience and reliance. The study explores the implementation of Akhlak and Tasawuf education in fostering the democratic character of PAI students at FITK UNSIQ in Wonosobo, Central Java in 2023. The research methodology employs a qualitative approach with descriptive field methods, collecting data through participant observation, interviews, and documentation. Findings indicate that discussion methods effectively link theory to practice, while implementation involves tailored planning and structured execution. Supporting factors include student equality, campus traditions, and a high number of students from Islamic boarding schools, while hindrances encompass student disinterest, lack of awareness, and a shortage of competent lecturers.